Printing Therapeutic Proteins in 3D using Nanoengineered Bioink to Control and Direct Cell Migration. Issue 11 (8th May 2019) - Peak, Charles W.; Singh, Kanwar Abhay; Adlouni, Mu'ath; Chen, Jeffrey; Gaharwar, Akhilesh K.
Abstract: A nanoengineered bioink loaded with therapeutic proteins is designed to direct cell function in a 3D printed construct. The bioink is developed from a hydrolytically degradable polymer and 2D synthetic nanoparticle. The synthesis of poly(ethylene glycol)‐dithiothreitol (PEGDTT) via a Michael‐like step growth polymerization results in acrylate terminated degradable macromer. The addition of 2D nanosilicates to PEGDTT results in formation of shear‐thinning bioinks with high printability and structural fidelity. The mechanical properties, swelling kinetics, and degradation rate of 3D printed constructs can be modulated by changing the ratio of PEG:PEGDTT and nanosilicates concentration. Due to high surface area and charged characteristic of nanosilicates, protein therapeutics can be sequestered in 3D printing structure for prolong duration. Sustained release of pro‐angiogenic therapeutics from 3D printed structure, promoted rapid migration of human endothelial umbilical vein cell. This approach to design biologically active inks to control and direct cell behavior can be used to engineer 3D complex tissue structure for regenerative medicine. Abstract : A nanoengineered bioink loaded with therapeutic proteins is designed to direct cell function in a 3D printed construct. This approach to design biologically active inks to control and direct cell migration can be used to engineer 3D vascularized tissue structure for regenerative medicine.